Autosomal Recessive Congenital Icthyosis with Cataract – A Case Report from Pakistan - Fatima, Nida; Arif, Afreen Muhammad; Nasir, Sharmeen; Aslam, Fariha (Journal of Medicine, 2023)
The ichthyoses are a diverse group of disorders with variable clinical presentations. There are syndromic and non-syndromic forms with multiple associated features. The association of autosomal recessive congenital icthyosis (ARCI) with cataract is a rare phenomenon and no such case has been reported in recent literature. We hereby report the case of a 5-year-old female patient, a product of consanguineous marriage, who presented to the pediatric department of Dr. Ruth K.M Pfau Civil Hospital Karachi, Pakistan, with the complaint of rough skin with scaling and peeling over the entire body since birth due to congenital icthyosis. Shefurther developed complaints of reduced vision which later was diagnosed as cataract. Her previous two siblings had similar illness and they expired. Widespread scaling is the defining feature of ichthyosis specifically when it comes to ARCI it manifests at birth and can later progress to any spectra of illness. A multidisciplinary approach is required for the management of such patient. J MEDICINE 2023; 24(2): 155-157